Supporting Social and Emotional Development of Preschool Children: A Small Scale Study in Malaysia - Sau Mun, Woo (2009)
The contribution of preschool education to children’s well being is widely recognised. Postmodern world of rapid change brings with it increasing incidences of social, emotional and behavioural difficulties in children and poses a great challenge to school. Literature review takes a leaning towards the postmodern perspective that views children social and emotional development as socially constructed that places dialogues at the heart of children’s social and emotional development, the focus is on giving the child a voice. Implications for children with communication difficulties are also explored.